# Algebra 2 ..

posted by .

Solve the equation by completing the square.
x^2-2=9x
My answer: x=9/2+or- the sqrt. of 22.25
(but when I checked my answer the actual answer was x=9+or - the sqrt. of 89 and then all over 2)

• Algebra 2 .. -

x^2 - 9x = 2
x^2 - 9x + (9/2)^2 = 2 + (9/2)^2
(x - 9/2)^2 = 89/4
x = 9/2 ± √(89/4)
x = 9/2 ± √22.25

but you could also factor out the 1/4 in 89/4 and say

x = 9/2 ± √89/√4
x = 9/2 ± √89/2
x = (9 ± √89)/2

these exercises usually want things as fractions rather than decimals, and the quadratic formula usually expresses the answers as they did.

## Similar Questions

1. ### Inequality

When I solve the inquality 2x^2 - 6 < 0, I get x < + or - sqrt(3) So how do I write the solution?
2. ### math,help,algebra I

I need help can someone help me get unstuck and let me know if i am correct.thank you. solve by completing the square. 4x^2+2x-3=0 this is what i am doing: i used the quadratic equation. so where i am is in this step: x = (-2 (+-) …

Problem #1 Solve by completing the square 2x^2-4x-11=0 My answer: x = (2+/-sqrt 26)/(2) Problem #2 Solve by using the quadratic formula x^2-4x-60=0 My answer: x = (2+/-sqrt 16)/(2) You did not do it completeing the square. Please show …
4. ### math,correction

Is this correct now. Problem #1 solve by completing the square. 2x^2+8x+3=0 My answer: x=-2 +/- sqrt (5)/(2) Problem #2 solve by using the quadratic formula 5x^2+3x+1=0 My answer: No solution are defined. You are not completing the …

Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine …
6. ### Calculus

Please look at my work below: Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8)) r=8 +/- Sqrt(2)*i, alpha=8, Beta=Sqrt(2) y(0)=2, e^(8*0)*(c1*cos(0)+c2*sin(0))=c2=2 …
7. ### algebra

can someone tell me if i did the problem correct (solve by completing the square) 4x^2+2x-3=0 x^2+(1/2)=3/4 x^2+(1/2)+(1/4)^2=3/4+(1/4)^2 (x+1/4)^2=13/16 x+1/4=+-sqrt 13/16 x+1/4=+-sqrt 13/4 x=-1/4+-sqrt 13/4 x=-1+-sqrt 13/4